Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, dan Komite Audit Terhadap Laporan Keberlanjutan - Suminar, DD Puspa; Purwaningsih, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Sustainability reports are created to provide information about the company's activities and as a form of corporate responsibility for the environment and social. This research aims to determine the extent to which profitability, liquidity, company size, and audit committee influence the level of sustainability report disclosure. This research applies a quantitative approach that utilizes secondary data sources, selected using a purposeful sampling method, resulting in a sample of 69 food and beverage sector companies listed on the IDX during the period 2021 to 2023. This research uses multiple linear regression models followed by classical assumption testing consisting of normality, multicollinearity, heteroscedasticity and autocorrelation tests, as well as hypothesis testing. Based on the findings of this research, it is known that profitability, liquidity and audit committee variables do not have a significant influence on sustainability reporting. Meanwhile, the firm size variable significantly influences sustainability reporting. This research is expected to increase the awareness of entities to publish more comprehensive sustainability reports.